THE ROLE OF THE RELIGION AFFAIRS INSTITUTION IN REDUCTING DIVORCES IN TEBET DISTRICT - Alyssa Naura az Zahra; Wahyunengsih Wahyunengsih (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2022)
This research aims to determine the importance of the pre-marriage program at the Religion Affairs Institution in Tebet District. To find out the factors that cause divorce in Tebet District and how to control it. Want to know how much the pre-marriage program influence in decline the divorce rate and what circumstates are taught in the pre-marriage guidance program. The result of this research indicate a decline of divorce rate in Tebet through the urgency of the pre-marriage program. Where the result from the writer’s interview show that the program implemented in the pre-marriage guidance are the resilt from direct local Religious Affairs Institution arrangement. This indicates that the analysis carried out by the Tebet Religion Affairs Institution resulted in a more relevant and effective pre-marriage guidance program in reducing divorce rate.